Altered rhizoctonia assemblages in grasslands on ex-arable land support germination of mycorrhizal generalist, not specialist orchids - Vogt-Schilb, Hélène (The New phytologist, 2020)
© 2020 The Authors. New Phytologist © 2020 New Phytologist Trust.